Distribution, Use Pattern and Potential for Conservation of Medicinal Climbers in Uttaranchalstate - Adhikari, B. S.; Babu, M. M.; Saklani, P. L.; Rawat, G. S. (Indian Forester, 2005)
This paper provides information on the distribution and use pattern of medicinal climbers in Uttaranchal State, India. A list of 88 medicinal climbers, found in Uttaranchal has been appended based on extensive literature survey. Their altitudinal distribution and parts used in various ailments has been analyzed. Fabaceae, Vitaceae and Cucurbitaceae are the largest families, and have more than 10 species of medicinal climbers. The medicinal climbers in different ecological regions found in sub-tropical, warm temperate, cool-temperate, sub-alpine and alpine are 83, 44,7,3 and 1, respectively. Including all the species the major parts used in various ailments are in the following order: Leaves and roots (44 species each) > fruits (17 species) > seed (15 species). Maximum climbers are used in dysentery, diarrhoea, fever, wounds, digestive complaints, skin diseases, rheumatism, bronchitis and asthma. The first region i.e., sub-tropical region is the most important zone for in-situ and ex-situ conservation of medicinal climbers, as most of them grow in this region. The paper will help in the formulation of strategies for promotion and cultivation of medicinal climbers in Uttaranchal State.